2009
DOI: 10.1161/circep.109.872309
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-Dependent Biophysical Phenotype for V227F-KCNJ2 Mutation in Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Background— KCNJ2 encodes Kir2.1, a pore-forming subunit of the cardiac inward rectifier current, I K1 . KCNJ2 mutations are associated with Andersen-Tawil syndrome and catecholaminergic polymorphic ventricular tachycardia. The aim of this study was to characterize the biophysical and cellular phenotype of a KCNJ2 missense mutation, V227F, found in a patient with catecholaminergic polymorphic ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…46,55 A specific KCNJ2 mutation, V227F, was identified in a patient with a typical catecholaminergic polymorphic VT phenotype. 56 Heterologous expression with the COS cell line showed that heterozygous wild-type/V227F channels were identical to wild-type channels in function, but stimulation by cAMP-dependent protein kinase A significantly downregulated heterozygous mutant Kir2.1 and not wild-type Kir2.1 currents. 56 This particular type of loss of function explained why the proband displayed the catecholaminergic polymorphic VT phenotype, in which typical bidirectional or polymorphic VT is provoked by exercise.…”
Section: Genetics In Congenital Lqtsmentioning
confidence: 97%
See 2 more Smart Citations
“…46,55 A specific KCNJ2 mutation, V227F, was identified in a patient with a typical catecholaminergic polymorphic VT phenotype. 56 Heterologous expression with the COS cell line showed that heterozygous wild-type/V227F channels were identical to wild-type channels in function, but stimulation by cAMP-dependent protein kinase A significantly downregulated heterozygous mutant Kir2.1 and not wild-type Kir2.1 currents. 56 This particular type of loss of function explained why the proband displayed the catecholaminergic polymorphic VT phenotype, in which typical bidirectional or polymorphic VT is provoked by exercise.…”
Section: Genetics In Congenital Lqtsmentioning
confidence: 97%
“…56 Heterologous expression with the COS cell line showed that heterozygous wild-type/V227F channels were identical to wild-type channels in function, but stimulation by cAMP-dependent protein kinase A significantly downregulated heterozygous mutant Kir2.1 and not wild-type Kir2.1 currents. 56 This particular type of loss of function explained why the proband displayed the catecholaminergic polymorphic VT phenotype, in which typical bidirectional or polymorphic VT is provoked by exercise. Most recently, a mutation in KCNJ5 was reported to result in a loss of function of I K-ACh responsible for LQT13, 54 although the precise role of I K-ACh in the ventricle is still unknown.…”
Section: Genetics In Congenital Lqtsmentioning
confidence: 97%
See 1 more Smart Citation
“…89 Although the finding has been considered a benign ECG manifestation, Haissaguerre et al first reported that the ER pattern In addition, a third variant of CPVT was reported to result from a mutation in KCNJ2, which encodes Kir2.1, a subunit for inward-rectifier potassium channels. 102 In 50 Japanese CPVT probands, mutations in RYR2, CASQ, and KCNJ2 were identified in 28 (56%), 1 (2%), and 1 (2%), respectively. 103 CPVT is a rare disease with an estimated prevalence of 1/10,000, but has become recognized as a significant cause of SCD in children and young adults.…”
Section: Ersmentioning
confidence: 99%
“…14 Recently, KCNJ2 mutations were reported not only in patients with ATS, but also in patients with catecholaminergic polymorphic ventricular tachycardia. 20 In the present study, we identified a novel nonsense KCNJ2 mutation, S369X, in a 13-year-old boy who had a prominent QU prolongation and mild muscle weakness but lacked dysmorphic features and examined its functional characterization by using electrophysiological and subcellular distribution analyses.…”
Section: Clinical Perspective On P 260mentioning
confidence: 93%